Junk car problem - Beckwith, Richard E.; Volek, Josef (Univerzita Pardubice, 1998)
The approach to the allocation/location problem solution of the recycling centres of used cars in the Czech Republic issues from the actual state, presumed development and designed target state. The actual state of used cars treatment in the CR is not very encouraging. The article presents the contributíon to the discussion of analytical possibilities of recycling centres location and used personal cars and lorries treatment system modelling.
Problém ojetých vozů
Keywords: used cars; recycling centres; liquidation; ojetá vozidla; recyklační střediska; likvidace